ТЕРМІЧНА ОБРОБКА АРТИЛЕРІЙСЬКИХ СТВОЛІВ ГАУБИЦЬ ДЛЯ ВИТРИМАННЯ ІНТЕНСИВНОГО ВОГНЮ - Сірий, Андрій (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2025)
The purpose of this study is to study the influence of various methods of heat treatment on the characteristics of the barrels of artillery howitzers, in particular on their hardness, strength, viscosity and wear resistance. The research is aimed at determining the optimal processing technologies to increase the endurance and effectiveness of barrels during intense fire. The work uses an analytical approach based on the processing of information sources on the research topic. The results of the study show that various methods of heat treatment have a significant effect on the characteristics of howitzer barrels. In particular, quenching and tempering significantly increase the hardness and strength of the metal, and tempering further increases the viscosity, making the barrels more resistant to cracks and impacts. Nitriding and cementation increase wear resistance, which extends the service life of barrels. Thus, it is determined that the heat treatment process has several stages.